Exploring corporate reputation variables to measure personal reputations - De la Rey Van der Waldt (Communicare)
This explorative article qualitatively describes reputation variables that are applicable to both corporate and personal reputations: identity, image, branding, personality, behaviour, culture, ethics and storytelling. The research problem is concerned with the fact that personal reputations are not studied with the same intensity as corporate reputations are. In the context of corporate communication, the question arises as to whether variables that measure corporate reputation can be applied to the assessment of personal reputations. The article aims firstly to describe the concepts which define reputations, both corporate and personal, from a corporate communication perspective, and secondly to describe ways of assessing corporate reputation, in order to suggest their application to personal reputation. In doing so, the article attempts to ground corporate reputation within the meta-theoretical context of corporate communication, according to the traditions of Van Riel (1995) and Van Riel and Fombrun (2007). The article concludes that the Reputation Quotient (RQ) can be applied to measure personal reputations. This measurement instrument includes all the assessment criteria of the Reputation Institute’s (2017) the RepTrak®, as well as the criteria of the Authentic Personal Governance Model, and the Personal Balanced Scorecard Framework proposed by Rampersad and Hussain (2014). The article does not attempt to elaborate upon a personality analysis of individuals, but is concerned with the possible application of corporate reputation measurement variables to measure the reputation of individuals.